The Attitudes towards National Belonging in the Primary School and its Relationship to Some Variables from the Point of View of Educational Leaders in Northern Sudan - Ghalib, Mutasim Al-Rasheed (Journal of Ecohumanism, 2025)
This study aims to reveal the attitudes towards national belonging from the perspective of educational leaders in primary school and their relationship to some variables (religious and historical values, teachers, extracurricular activities). The study sample consisted of (58) educational leaders in northern Sudan. The researcher designed a questionnaire to collect study data, using the descriptive analytical approach. The study data were analyzed using the social sciences package. PSS), and the results of the study showed that the level of influence of the four study variables in building attitudes towards national belonging from the point of view of educational leaders in the primary school.(Religious values ​​- historical factors - the role of the teacher - extracurricular activities) High, historical factors contribute to building positive attitudes towards national belonging (to a large extent) from the point of view of educational leaders in building positive attitudes, the teacher contributes to building attitudes towards national belonging (to a large extent) from the point of view of educational leaders, extracurricular activities contribute to building positive attitudes towards national belonging (to a large extent) from the point of view of educational leaders, there are statistically significant differences between the four variables (religious values ​​- historical factors - the role of the teacher - extracurricular activities) in terms of their impact on building attitudes towards national belonging in favor of religious values ​​according to the attitudes of educational leaders. The study recommends activating the role of the teacher and the school environment with all its motivating components to build factors of national belonging from an early age, and the primary school is important in this matter.